Mindfulness Practice and Burnout: Evidence From Chinese Social Workers - Tu, Bin; Huang, Chienchung; Sitar, Sophie; Yang, Meifen (Frontiers in Psychology, 2022)
Over the span of nearly 10 years, the social work labor force grew from 0.2 million to approximately 1.2 million in China. Despite these increases, studies have shown social workers in China are also experiencing equally high burnout rates. For this analysis, we collected data from 537 social workers based in Guangzhou, China. We used the job demands and resources (JD-R) theory, to examine the relations between JD-R and burnout and whether mindfulness practice (MP) could reduce any such burnout. Our results suggest JD-R affects social workers’ burnout through both health and motivation impairment. High job demands (JD) were linked to high burnout while high job resources (JR) were linked to a reduction in burnout. Formal (Beta=-0.08) and informal (Beta=-0.19) MP were associated with low burnout amongst social workers. The significant interaction between JD and MP also suggests that MP can reduce burnout for social workers with high JD. The findings call for using MP to be used to shield social workers from the effects of increasing JD and to prevent an increase of burnout amongst Chinese social workers.